TVA and the Dispossessed: The Resettlement of Population in the Norris Dam Area - Smith, Geoffrey S. (Labour / Le Travail, 1985)
This article reviews the book, "TVA and the Dispossessed: The Resettlement of Population in the Norris Dam Area," by Michael J. McDonald & John Muldowny.
Keywords: LAND settlement; MCDONALD, Michael J.; MULDOWNY, John; Nonfiction; REVIEWS; TVA & the Dispossessed: The Resettlement of Population in the Norris Dam Area (Book); books